Impact of updated radiative transfer scheme in snow and ice in RACMO2.3p3 on the surface mass and energy budget of the Greenland ice sheet - C. T. van Dalum; W. J. van de Berg; M. R. van den Broeke (The Cryosphere, 2021)
Radiative transfer in snow and ice is often not modeled explicitly in regional climate models. In this study, we evaluate a new englacial radiative transfer scheme and assess the surface mass and energy budget for the Greenland ice sheet in the latest version of the regional climate model RACMO2, version 2.3p3. We also evaluate the modeled (sub)surface temperature and melt, as radiation penetration now enables internal heating. The results are compared to the previous model version and are evaluated against stake measurements and automatic weather station data of the K-transect and PROMICE projects. In addition, subsurface snow temperature profiles are compared at the K-transect, Summit, and southeast Greenland. The surface mass balance is in good agreement with observations, with a mean bias of −31 mm w.e. yr−1 (−2.67 %), and only changes considerably with respect to the previous RACMO2 version around the ice margins and near the percolation zone. Melt and refreezing, on the other hand, are changed more substantially in various regions due to the changed albedo representation, subsurface energy absorption, and meltwater percolation. Internal heating leads to higher snow temperatures in summer, in agreement with observations, and introduces a shallow layer of subsurface melt. Hence, this study shows the consequences and necessity of radiative transfer in snow and ice for regional climate modeling of the Greenland ice sheet.